Neohilgertia venusti Gen. N. SP. N. (Nematoda: Oxyuridae)from Thylamys venustus cinderellus (Thomas) Reig, Kirsch & Marshall, 1985 (Marsupialia: Didelphidae) in Burruyacu, Tucuman, Argentina - Systematic position and possible evolution - Graciela T. Navone; Delia Mabel Suriano; Carlos A. Pujol (Memorias do Instituto Oswaldo Cruz, 1990)
Neohilgertia gen. n. proposed for Oxyuridae nematodes from Thylamys venustus cinderellus (Marsupialia: Didelphidae) is described. The hypothesis about the possibility of a secondary parasitism for marsupials and the origin of the genus in the African Sciuridae parasite ancestors is discussed.